Accelerating Promotional Media on Social Media for Brand Awareness Forest Smoothie - Suria Ningsih; I Nyoman Yoga Sumadewa; Ni Putu Sinta Dewi (MultiTech Publisher, 2024)
With high deforestation rates, reforestation is important to restore the ecosystem. Forest Smoothie, an international beverage company with the concept of